A patent update on therapeutic applications of urease inhibitors (2012–2018). (4th March 2019) - Hameed, Abdul; Al-Rashida, Mariya; Uroos, Maliha; Qazi, Syeda Uroos; Naz, Sadia; Ishtiaq, Marium; Khan, Khalid Mohammed
ABSTRACT: Introduction : Urease is a nickel-containing metalloenzyme that is commonly found in different bacteria, plants, algae, and fungi and mediates the growth of many pathogenic bacteria in the acidic environment of the stomach. Despite the large number of molecules known to have excellent urease inhibitory activity, there is an alarming lack of urease inhibitor drugs on the market. Area covered : This review aims to provide a comprehensive overview of the different types of molecules patented as potent urease inhibitors from the year 2012 to 2018. Expert opinion : Urease is an important target to treat urease-related bacterial infections manifesting as gastric ulcers, urinary tract infections, and kidney stones. Although many different molecules as inhibitors of urease have been reported, only a few have advanced to clinical trials. The development of new effective urease inhibitors demands new suitable lead molecules. This review covers the patents on urease inhibitors in recent years (2012–2018) with a hope to bring into focus the issue and need for availability of new urease inhibitors on the market.